2012
DOI: 10.2174/157016212799937272
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D Concentration and Potential Risk Factors for its Deficiency in HIV Positive Individuals

Abstract: Human immunodeficiency virus (HIV) infected individuals are prone to malnutrition, and deficiencies of some minerals and vitamins. The aim of this study is to evaluate the frequency of vitamin D deficiency and determine the possible risk factors associated with this problem in HIV-infected individuals. This cross-sectional study was performed on 98 adult patients referred to the Emam Khomeini Hospital Complex, Tehran, Iran. The patients' serum vitamin D concentration was determined using radioimmunoassay metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
1
5
0
2
Order By: Relevance
“…Vitamin D deficiency was found in HIV/HCV co-infected patients [51]. Moreover, higher vitamin D levels were independently associated with a rapid virological response in patients with genotype 1 chronic hepatitis C [52].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency was found in HIV/HCV co-infected patients [51]. Moreover, higher vitamin D levels were independently associated with a rapid virological response in patients with genotype 1 chronic hepatitis C [52].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study that was conducted on HIV positive patients in Iran, it was found out that 86.7% of patients were suffering from Vit-D deficiency. In that research, the serum Vit-D level was associated with factors such as the intake of Vit-D, duration of exposure to sunlight, PTH level, and daily consumption of calcium (38). Various studies have reported the high level of Vit-D deficiency in the Iranian society.…”
Section: Resultsmentioning
confidence: 95%
“…Yaşanılan enleme, mevsime ve deri pigmentasyonu özelliklerine göre D vitamini düzeyi değişkenlik göstermektedir (8). Ayrıca kadın cinsiyet, işsizlik, sigara kullanımı, hepatit C koenfeksiyonu da bu hasta grubunda ek risk faktörleri olarak bulunmuştur (15,16). Vitamin D düzeyini değerlendirmede, sirkülasyondaki major form olması ve yarılanma ömrünün 2-3 hafta olması nedeniyle serum 25(OH)D en uygun parametredir.…”
Section: Discussionunclassified
“…Vitamin D düzeyini değerlendirmede, sirkülasyondaki major form olması ve yarılanma ömrünün 2-3 hafta olması nedeniyle serum 25(OH)D en uygun parametredir. İran'da yapılan bir çalışmada da %86,7 hastada D vitamini <35nmol/L bulunmuştur (15). Üzerinde net bir görüş birliği olmamakla beraber 50 nmol/L'nin altındaki değerler D vitamini eksikliğini işaret eder.…”
Section: Discussionunclassified